Mercury Porosimetry in Mesoporous Glasses: A Comparison of Experiments with Results from a Molecular Model. - Thommes, Matthias; et al. (Langmuir, 2007)
We present results from expts. and mol. modeling of mercury porosimetry into mesoporous Vycor and controlled pore glass (CPG) solid materials. The exptl. intrusion/extrusion curves show a transition from a type H2 hysteresis for the Vycor glass to a type H1 hysteresis for the CPG. Mercury entrapment is obsd. in both materials, but we find that the amt. of entrapped mercury depends on the chosen exptl. relaxation time. No addnl. entrapment is found in a second intrusion/extrusion cycle, but hysteresis is still obsd. This indicates that hysteresis and entrapment are of different origin. The exptl. observations are qual. reproduced in theor. calcns. based on lattice models, which provide significant insights of the mol. mechanisms occurring during mercury porosimetry expts. in these porous glasses. [on SciFinder(R)]
Keywords: mercury porosimetry mesoporous glass pore size distribution